Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Petani Padi (Studi Kasus Subak Gubug Desa Sudimara, Tabanan, Bali) - Anak Agung Gede Putra; I Wayan Terimajaya (Universitas Tabanan, 2026)
Rice farmer income remains a central issue in agricultural development in Indonesia, particularly in Bali, home to the traditional subak irrigation system, a world cultural heritage. Fluctuating grain prices, high production costs, and farmers' limited access to capital and modern technology often lead to income instability. This study aims to analyze factors influencing rice farmer income, including land area, production costs, technology use, access to capital, grain prices, and the role of subak institutions. The study used a quantitative approach with a survey method among 60 farmer respondents, members of Subak Gubug, Sudimara Village, Tabanan. Data were collected through structured questionnaires, interviews, and field observations. Data analysis was conducted using multiple linear regression to determine the effect of independent variables on farmer income. The results showed that land area, grain prices, and the role of subak institutions had a positive and significant effect on rice farmer income. Production costs had a significant negative effect, while access to capital and technology use had a positive but insignificant effect. These findings indicate that farmer income stability is strongly influenced by structural factors (land area and subak institutions) and market factors (grain prices). This research provides policy implications that efforts to increase rice farmer incomes require an integrated strategy through strengthening subak institutions, agricultural input subsidy policies, expanding access to capital, and stabilizing grain prices. This will ensure the sustainability of rice farming in Bali, both economically and culturally.